Photoperiodic regulation of the sucrose transporter StSUT4 affects the expression of circadian-regulated genes and ethylene production - Chincinska, Izabela; Gier, Konstanze; Krügel, Undine; Liesche, Johannes; He, Hongxia; Grimm, Bernhard; Harren, Frans J.; Cristescu, Simona; Kuehn, Christina (Frontiers in Plant Science, 2013)
Several recent publications report different subcellular localisation of members of the SUT4 subfamily of sucrose transporters. The physiological function of SUT4 sucrose transporters is still not entirely clarified as down-regulation of members of the SUT4 clade had very different effects in rice, poplar and potato. Here, we provide new data on the localization and function of the Solanaceous StSUT4 protein, further elucidating involvement in the onset of flowering, tuberization and in the shade avoidance syndrome of potato plants. Induction of early flowering and tuberization in SUT4-inhibited potato plants correlates with increased sucrose export from leaves and increased sucrose and starch accumulation in terminal sink organs such as developing tubers. SUT4 does not only affect the expression of gibberellin and ethylene biosynthetic enzymes, but also the rate of ethylene synthesis in potato. In SUT4-inhibited plants, the ethylene production no longer follows a diurnal rhythm, leading to the assumption that StSUT4 controls circadian gene expression, potentially by regulating sucrose export from leaves. Furthermore, SUT4 expression affects clock-regulated genes such as StFT, StSOC1 and StCO, which might also be involved in a photoperiod-dependently controlled tuberization. A model is proposed in which StSUT4 controls a phloem-mobile signalling molecule generated in leaves which together with enhanced sucrose export affects developmental switches in apical meristems. SUT4 seems to link photoreceptor-perceived information about the light quality and day length, with phytohormone biosynthesis and the expression of circadian genes.